2021
DOI: 10.3390/cancers13174293
|View full text |Cite
|
Sign up to set email alerts
|

ATP Inhibits Breast Cancer Migration and Bone Metastasis through Down-Regulation of CXCR4 and Purinergic Receptor P2Y11

Abstract: ATP released by bone osteocytes is shown to activate purinergic signaling and inhibit the metastasis of breast cancer cells into the bone. However, the underlying molecular mechanism is not well understood. Here, we demonstrate the important roles of the CXCR4 and P2Y11 purinergic receptors in mediating the inhibitory effect of ATP on breast cancer cell migration and bone metastasis. Wound-healing and transwell migration assays showed that non-hydrolysable ATP analogue, ATPγS, inhibited migration of bone-tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…BzATP is the agonist to active P2X7 receptor, theoretically which would be harmful for the treatment of cancer in that increasing evidence demonstrated that suppression of high concentration of ATP in tumor microenvironment and the activation of P2X7 is recognized as a promising strategy for the treatment of different tumors [ 12 , 18 , 20 , 38 , 39 ]. However, ATP is considered a double-edged sword in cancer [ 40 , 41 ] and BzATP could inhibit breast cancer cell migration [ 42 ]. It indicated that both the agonist (BzATP) and antagonist (JNJ) of P2X7 receptor would be useful to inhibit the proliferation of human cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…BzATP is the agonist to active P2X7 receptor, theoretically which would be harmful for the treatment of cancer in that increasing evidence demonstrated that suppression of high concentration of ATP in tumor microenvironment and the activation of P2X7 is recognized as a promising strategy for the treatment of different tumors [ 12 , 18 , 20 , 38 , 39 ]. However, ATP is considered a double-edged sword in cancer [ 40 , 41 ] and BzATP could inhibit breast cancer cell migration [ 42 ]. It indicated that both the agonist (BzATP) and antagonist (JNJ) of P2X7 receptor would be useful to inhibit the proliferation of human cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In other cancers, the role of P2RY11 is gradually developing. P2RY11 was shown to be highly expressed in hepatocellular carcinoma tissue compared to normal tissue and promotes migration in vitro [76], this was similarly the case in breast cancer where siRNA knockdown of P2RY11 inhibited cell migration, as did NF157 which reduced breast cancer cell migration in a dose-dependent manner [77]. P2RY11 expression and function has not been explored in any other PBC models and therefore it could provide a novel target for OS or Ewing's sarcoma where NF157 could be used.…”
Section: P2ry11mentioning
confidence: 86%
“…Primary bone tumors are relatively rare, but because of the highly vascularized and metastatic environment (TGFβ-rich calcified matrix), bone tissue is the third most common site of solid tumor metastasis, with up to 70% of metastatic breast and prostate cancer patients harboring bone metastasis, leading to shortened survival time and serious bone complications during the remaining lifespan ( 91 94 ). Distant metastasis such as bone tissue is considered one of the primary causes of treatment failure in advanced breast cancer ( 5 , 55 ). Among all the bone cells, OCY seems less affected by metastasizing cancer cells because they are further away from the actively metabolized bone marrow.…”
Section: Tumor–ocy Interactionmentioning
confidence: 99%